MODERN VIEWS OF THE IMMUNOPATHOGENESIS OF PSORIASIS DISEASE - Yemchenko, Ya.А.; Іщейкін, К.Є.; Кайдашев, І.П.; Kaidashev; I.P. (World of Medicine and Biology, 2018)
The article reviews literature about the role of immune disorders in the pathogenesis of psoriasis. This article shows the new data about the research of inflammation, which begins in the skin of patients with psoriasis and it leads to the development of systemшiс inflammation and it shows the role of newly discovered IL-33 and the polarization of macrophages in the pathogenesis of psoriasis. This information helps to expand the idea about the mechanism of psoriasis, to find new methods of therapy, to determine assessment of gravity, activity of disease.
Keywords: psoriasis; immunopathogenesis; IL-33; polarization of macrophages